Lack of association of polymorphisms in homocysteine metabolism genes with pseudoexfoliation syndrome and glaucoma - Fan, Bao Jian (Molecular Vision, 2008)
PURPOSE: To evaluate genes involved in homocysteine metabolism as secondary risk factors for pseudoexfoliation syndrome (PXFS) and the associated glaucoma (PXFG). METHODS: One hundred eighty-six unrelated patients with PXFS, including 140 patients with PXFG and 127 unrelated control subjects were recruited from the Massachusetts Eye and Ear Infirmary. All the patients and controls were Caucasian of European ancestry. Seventeen tag SNPs from 5 genes (methylenetetrahydrofolate reductase [MTHFR], methionine synthase [MTR], methionine synthase reductase [MTRR], methylenetetrahydrofolate dehydrogenase [MTHFD1], and cystathionine β-synthase [CBS]) were genotyped. Single-SNP association was analyzed using Fisher’s exact test (unconditional) or logistic regression after conditioning on the effects of age and three LOXL1 SNPs (rs1048661, rs3825942, and rs2165241). Interaction analysis was performed between the homocysteine and LOXL1 SNPs using logistic regression. Haplotype analysis and the set-based test were used to test for association of individual genes. Multiple comparisons were corrected using the Bonferroni method. RESULTS: One SNP (rs8006686) in MTHFD1 showed a nominally significant association with PXFG (p=0.015, OR=2.23). None of the seventeen SNPs tested were significantly associated with PXFS or PXFG after correcting for multiple comparisons (Bonferroni corrected p>0.25). After controlling for the effects of age and three associated LOXL1 SNPs, none of the seventeen tested SNPs were associated with PXFS (p>0.12). No significant interaction effects on PXFS were identified between the homocysteine and LOXL1 SNPs (p>0.06). Haplotype analysis and the set-based test did not find significant association of individual genes with PXFS (p>0.23 and 0.20, respectively). CONCLUSIONS: Five genes that are critical components of the homocysteine metabolism pathway were evaluated as secondary factors for PXFS and PXFG. Our results suggest that these genes are not significant risk factors for the development of these conditions.